Adverse childhood experiences in a South Australian sample of young people in detention - Malvaso, Catia G. (The Australian and New Zealand journal of criminology, 2019)
Empirical knowledge about the prevalence and interrelatedness of adverse childhood experiences in young people involved in youth justice systems in Australia is limited. This study examined the prevalence of adverse childhood experiences in a sample of young people who were detained in youth justice services in South Australia. It also explored how adverse childhood experiences are interrelated and their associations with violent offending. Assessment data for 2045 young people who spent time in detention between 1995 and 2012 were used. The results indicated that adverse childhood experiences were common in this population, were highly interrelated, and more prevalent among young people who had convictions for violent offences. Differences in the prevalence of adverse childhood experiences according to gender and cultural background were evident. Compared to males, females had a higher prevalence of individual adverse childhood experiences, as well as higher cumulative adverse childhood experience scores. Non-Aboriginal females had the highest prevalence for physical and sexual abuse, and household conflict, while both Aboriginal males and females reported more family criminality and substance use problems. These findings have important implications for the role of screening for adverse childhood experiences in offender populations, and the potential benefit of targeting interventions towards addressing the consequences of these traumatic experiences.